1989
DOI: 10.1037/0021-9010.74.3.502
|View full text |Cite
|
Sign up to set email alerts
|

Job and life satisfaction: A reevaluation of the strength of the relationship and gender effects as a function of the date of the study.

Abstract: Keeping You Up-to-Date: All APA members (Fellows; Members; and Associates, and Student Affiliates) receive-as part of their annual dues-subscriptions to the American Psychologist and the APA Monitor.High School Teacher and Foreign Affiliates receive subscriptions to the APA Monitor and they can subscribe to the American Psychologist at a significantly reduced rate.In addition, all members and affiliates are eligible for savings of up to 50% on other APA journals, as well as significant discounts on subscriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
246
3
10

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(279 citation statements)
references
References 27 publications
(49 reference statements)
18
246
3
10
Order By: Relevance
“…Factor 3, service under pressure, shows no gender difference, which disproves our starting hypothesis where we believed that men would be more resistant to providing service under pressure. Finally, level of job satisfaction was the same for both genders, which is in accordance with numerous previous research (Brief, Rose, & Aldag, 1977;De Vaus & McAllister, 1991;Mottazl, 1986;Smith, & Hoy, 1998;Tait, Padgett, & Baldwin, 1989;Ugorji, 1997;Witt & Nye, 1992). This also indicates our assumptions were erroneous, because we expected women to be more satisfied than men, like many authors proved previously (Clark, 1996(Clark, , 1997Hodson, 1989;Murray & Atkinson, 1981;Sloane & Williams, 1996).…”
Section: Research Resultssupporting
confidence: 72%
“…Factor 3, service under pressure, shows no gender difference, which disproves our starting hypothesis where we believed that men would be more resistant to providing service under pressure. Finally, level of job satisfaction was the same for both genders, which is in accordance with numerous previous research (Brief, Rose, & Aldag, 1977;De Vaus & McAllister, 1991;Mottazl, 1986;Smith, & Hoy, 1998;Tait, Padgett, & Baldwin, 1989;Ugorji, 1997;Witt & Nye, 1992). This also indicates our assumptions were erroneous, because we expected women to be more satisfied than men, like many authors proved previously (Clark, 1996(Clark, , 1997Hodson, 1989;Murray & Atkinson, 1981;Sloane & Williams, 1996).…”
Section: Research Resultssupporting
confidence: 72%
“…In one study, employees high in dispositional positive affect had jobs, as rated by trained observers, that had more autonomy, meaning, and variety (Staw, Sutton, & Pelled, 1994). Finally, evidence from a variety of sources shows that happy people are more satisfied with their jobs (e.g., Connolly & Viswesvaran, 2000;Tait, Padgett, & Baldwin, 1989;Weiss, Nicholas, & Daus, 1999). In a meta-analysis of 27 studies of affect and job satisfaction, Connolly and Viswesvaran concluded that 10%-25% of the variance in job satisfaction was accounted for by measures of dispositional affect.…”
Section: Employment and Quality Of Workmentioning
confidence: 99%
“…In a recent meta-analytic review, Tait, Padgett, and Baldwin (1989) found the average correlation between job and life satisfaction, corrected for measurement error, to be .44. Some researchers have interpreted the correlation between job and life satisfaction as evidence for a dispositional effect on job satisfaction (see Staw & Ross, 1985).…”
Section: --------------------mentioning
confidence: 99%